Association Between Neck Circumference and Microalbuminuria in Community Residents - Jian C (Dove Medical Press, 2021)
Chaohui Jian,* Yiting Xu,* Yun Shen, Yufei Wang, Xiaojing Ma, Yuqian Bao Department of Endocrinology and Metabolism, Shanghai Jiao Tong University Affiliated Sixth People’s Hospital; Shanghai Clinical Center for Diabetes; Shanghai Key Clinical Center for Metabolic Disease; Shanghai Diabetes Institute; Shanghai Key Laboratory of Diabetes Mellitus, Shanghai, 200233, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaojing Ma; Yuqian BaoDepartment of Endocrinology and Metabolism, Shanghai Jiao Tong University Affiliated Sixth People’s Hospital, Shanghai Diabetes Institute, 600 Yishan Road, Shanghai, 200233, People’s Republic of ChinaTel +86-21-64369181Fax +86-21-64368031Email maxiaojing@sjtu.edu.cn; yqbao@sjtu.edu.cnObjective: Neck circumference (NC) represents the subcutaneous fat deposition in the neck and is an effective indicator for evaluating metabolic disorders, such as metabolic syndrome, subclinical atherosclerosis, and non-alcoholic fatty liver disease. Microalbuminuria (MAU) is regarded as a potential sign of systemic endothelial dysfunction and microvascular abnormalities. The aim of this study was to elucidate the association of NC with urine albumin-to-creatinine ratio (UACR) and MAU.Methods: A total of 1882 Shanghai community residents were enrolled (816 men and 1066 women), with age ranging from 40 to 80 years. Anthropometric parameters, including NC, and biochemical indices were measured. MAU was determined if 30 mg/g ≤ UACR < 300 mg/g. An elevated NC was defined as NC ≥ 38.5 cm for men and NC ≥ 34.5 cm for women.Results: Individuals with an elevated NC had significantly higher prevalence of MAU and UACR values than those with normal NC in both men and women (all P < 0.05). The logistic regression analysis showed that there were significant and positive associations between elevated NC and the increasing risk of MAU after adjusting for lipid profile and glycemic indices (P = 0.007 for men and P = 0.009 for women). After further adjusting for blood pressure, elevated NC caused an 69.3% additional risk of MAU in men (P = 0.037) and the positive correlation in women disappeared (P = 0.131).Conclusion: There was an independent and positive association between elevated NC and the risk of MAU in men in the Chinese community population.Chinese Clinical Trial Registry (Www.chictr.org.cn) Registration Number: ChiCTR1900024011.Keywords: neck circumference, microalbuminuria, urine albumin-to-creatinine ratio